The determinant of online purchasing behaviour in Malaysia based on Technology Acceptance Model (TAM) - Abdul Jamil, Nordin; Nik Mat, Nik Kamariah (2012)
Internet online purchasing has been a growing phenomenon around the globe, especially among countries that have well developed infrastructure for marketing activities over the Internet. Despite the world internet potential, the growth of actual number of internet users who purchased online has been low.Thus, our study intends to investigate the determinant of online purchasing behaviour in Malaysia based on Technology Acceptance Model (TAM).This study examines the relationships between perceived risks (PR), perceived usefulness (PU), and perceived ease of use (PEOU), toward attitude, intention and actual online purchasing (AOP).Data were collected from 212 internet users in Malaysia via questionnaires.The results show that all direct hypotheses are supported while the indirect hypotheses are not supported. The generating model achieved the highest SMC (R2), explaining 53.9% variance in AOP. The results are discussed in the Malaysian online purchasing context.